Contribution to the knowledge of the butterfly fauna of Montenegro (Lepidoptera: Rhopalocera) - Švara, Vid (Acta entomologica slovenica (Ljubljana), 2015)
During the years 2009 to 2013, three visits to Montenegro were made to study the spring and early summer butterfly fauna. The focus of our study was on the south-western part of the country, especially the coastal region. A total of 31 localities were visited and some interesting observations were made. Altogether 112 species were recorded, confirming high diversity of the butterfly fauna of this country. Among the observed species, the following are rare or local in Montenegro: Papilio alexanor, Gonepteryx cleopatra, Brenthis ino, Apatura metis, Coenonympha orientalis, Pyrgus sidae, while Cupido osiris is reported for the first time for the country. Based on available literature information the butterfly fauna of Montenegro now includes 168 species.
Keywords: butterflies; conservation; Cupido osiris; Črna gora; Lepidoptera; metulji; Montenegro; rare species; redke vrste; Rhopalocera; varstvo